EDUCATIONAL NEUROSCIENCE DALAM PENDIDIKAN DASAR - Hamdan Husein Batubara; Asep Supena (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2018)
Abstract: This article aims to explain the implementation of educational neuroscience results in elementary school. The method of this article is a literature study by tracing various scientific papers relating to this study. The results of this study conclude that educational neuroscience is a field of neuroscience studies that focuses on studying the concept of education in a transdisciplinary from a neuroscience perspective. Educational neuroscience research results prove that the structure of the nervous system underlies human actions, both cognition, affection, and psychomotor. Implementation of the results of neuroscience research in elementary school involves neuroscience, cognitive neuroscience, psychology, educational theory, and learning practices. The concept of learning in the neuroscience perspective is learning that empowers the brain's ability by creating a challenging, enjoyable, meaningful learning environment, and encourages students to be active. Thus, educational neuroscience is a model of future education that is important to be learned by elementary school teachers. Keyword : educational neuroscience, elementary school